Penafsiran Ṭāhir Ibn ‘Āsyūr Terhadap Ayat-ayat tentang Demokrasi: Kajian atas Tafsir al-Taḥrīr wa al-Tanwīr - Lutfiyatun Nikmah (Journal of Islamic Studies and Humanities, 2017)
This study explains Ibn ‘Āsyūr interpretation of the verses about democracy in the Tafsir al-Taḥrīr wa al-Tanwīr with historical approach. Some of the issues explained include democratic relations with Islam, democratic practices in Muslim countries, acceptance of Ibn ‘Āsyūr on the existential principles of democracy namely the principle of freedom, equality, and popular sovereignty. This thesis finds that there is a difference between liberal democracy and Islamic democracy where freedom in Islam is restricted as long as its actions do not harm others. In Islam there is a supreme source that can not be changed by the will of the people ie shari'a law as applied qiṣās. The decision-making is based on quality (opinions that are more directed to the goal) while the technique is not standardized. Relation of state and religion according to Ibn ‘Āsyūr is integrative in terms of rejecting secularization between the two.* * *Penelitian ini menjelaskan penafsiran Ibn ‘Āsyūr tentang ayat-ayat tentang demokrasi dalam tafsir al-Taḥrīr wa al-Tanwīr dengan pendekatan sejarah. Isu yang akan dipaparkan di antaranya hubungan demokrasi dengan Islam, praktek demokrasi di negara muslim, penerimaan Ibn ‘Āsyūr mengenai prinsip-prinsip eksistensial demokrasi yaitu prinsip kebebasan, persamaan, dan kedaulatan rakyat. Tesis ini menemukan bahwa terdapat perbedaan antara demokrasi liberal dan demokrasi Islam dimana kebebasan dalam Islam dibatasi selama tindakannya tidak membahayakan orang lain. Dalam Islam ada sumber tertinggi yang tidak dapat diubah oleh kehendak rakyat yakni hukum syari’at seperti diterapkannya qiṣās. Adapun pengambilan keputusan didasarkan pada kualitas (pendapat yang lebih mengarah kepada tujuan) sedangkan tekniknya tidak dibakukan. Hubungan negara dan agama menurut Ibn ‘Āsyūr adalah integratif dalam artian menolak sekularisasi di antara keduanya.